PENGARUH MEDIA SENSORY GEOMETRY CARD TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN - Nurhaningtyas Agustin; Kholifaturrohmah; Akhmad Aji Pradana; Irfa’i Alfian Mubaidilla (LPPM IAD Probolinggo, 2025)
This study aims to determine the effect of Sensory Geometry Card media on the cognitive abilities of children aged 5-6 years at Bina Wiyata Kepohagung Plumpang Kindergarten. The problem raised is the lack of interesting and interactive media to introduce basic geometry concepts, so that some children have difficulty distinguishing shapes such as circles, triangles, and squares. The study used a quantitative approach of one-group pretest-posttest design with a sample of 27 children. Data collection techniques used observation, written tests, and documentation. The results of the study from the average pretest value of 18.18, and after being given treatment through the application of sensory geometry card media, the average posttest value increased to 26.74 so that there was an increase of 8.56 points. The results of the t-test showed t count = 13.250> t table = 2.056 and a significance value of 0.000 <0.05, so H₀ was rejected. This means that there is a significant influence of the use of Sensory Geometry Card media on the cognitive abilities of children aged 5-6 years at Bina Wiyata Kepohagung Plumpang Kindergarten. Keywords: sensory geometry card media; cognitive abilities; children aged 5-6 years